Winarni Literature review on the development of quiver and padlet media in fine arts learning for elementary school students in 2020-2025 - Winarni, Winarni; Andaryani , Eka Titi; Subali , Bambang; Widiarti , Nuni (Jurnal Inspirasi Pendidikan, 2026)
The rapid advancement of augmented reality (AR) and digital collaborative platforms necessitates their integration into elementary art education, particularly for Gen Z and Alpha students. This bibliometric study aimed to map research trends concerning the use of Quiver AR and Padlet in elementary visual arts learning from 2020 to 2025. Employing a systematic literature review with a bibliometric approach, data from Google Scholar and Scopus were analyzed using Publish or Perish and VOSviewer. Out of 1,014 initial articles, 14 met the inclusion criteria. The findings reveal fluctuating publication trends, peaking in 2020 and 2023, with Indonesia emerging as the dominant research contributor (42.9%). Quiver AR significantly overshadowed Padlet in research focus (64.3% vs. 14.3%), primarily targeting upper elementary grades. VOSviewer visualizations identified five interconnected research clusters and a temporal evolution from pandemic-response topics (2020-2021) to pedagogical effectiveness (2022-2023) and advanced AI integration (2024-2025). Critical research gaps were identified in Quiver-Padlet integration, creative assessment methods, and inclusive art education. Despite the proven potential of these technologies to enhance creativity and digital literacy, the limited and niche research landscape underscores a significant need for more comprehensive, contextual, and longitudinal studies, especially hybrid models leveraging both platforms for enriched elementary art learning.